2012
DOI: 10.1007/s10346-011-0311-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rock weathering, clay mineralogy, and geological structures in the formation of large landslide, a case study from Dumre Besei landslide, Lesser Himalaya Nepal

Abstract: The Dumre Besi landslide is one of the largest and most problematic failures on the MuglingNarayanghat Highway in central Nepal. Though it was triggered by the monsoon rain of 2003, geological structures and rock weathering have played a key role in its initiation and further aggravation. The slide is also controlled to some extent by the groundwater and rugged topography with high slope angles. The landslide zone comprises thinly laminated light grey siltstone with numerous crosscutting quartz veins, grey met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Past studies have focused on simulating various situations by modifying variables in spatial models [24][25][26]. The measures should also consider general adaptation plans to deal with climate change.…”
Section: The Effect Of Adaptationmentioning
confidence: 99%
“…Past studies have focused on simulating various situations by modifying variables in spatial models [24][25][26]. The measures should also consider general adaptation plans to deal with climate change.…”
Section: The Effect Of Adaptationmentioning
confidence: 99%
“…Rainfall and Earthquakes are main triggering factor for mass movements [3] [4] [5] [6], however the rock type, type of bedrock, type of cover material, geotechnical and hydrogeological properties, land use, slope gradient, slope shape, and so on can be considered as contributory other contributory factors [3] [7] [8] [9] [10]. Sri Lanka is located in earthquake free zone [11] Therefore in Sri Lankan contest, rainfall can be considered as a main landslide triggering factor.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists only very few literature from Nepal focusing in the role of rock weathering and geological structures in landslide formation. Regmi et al (2012) reported that there is a considerable effect of rock weathering and geological structures in the formation of large landslides. It is essential to make more rigorous studies in this aspect to get accurate information regarding the relationship between rock weathering and geological structures in landslide formation in the Himalaya.…”
Section: Introductionmentioning
confidence: 99%